ARTISTIC EXPRESSION OF LANDSCAPE IN THE STORIES OF ISAJAN SULTAN (Scientific journal of the Fergana State University, 2024)
The article reflects on the stories of Isajan Sultan. In his stories, the image of nature, its artistic interpretation, the task of which was drawn to analysis. The role of landscape in the compositional level of the story, its poetic functions in the illumination of the inner world of images are based on examples.